The Effect of a Remedial Counselling Program in StudySkills on Academic Achievement - Mohammed M. Abu~Alia (Journal of Islamic Studies, 1993)
The purpose of this research was to treat the effect of a remedial counselling program in studyskills on the academic achievement of ninth grade pupils. The remedial Counselling prOgram in thisresearch was developed by the researcher and it has been applied to 10 pupils who were considered as anexperimental group. The program was conducted during the second semester of the 19894990 schoolyear. T. Test was used to test the differences between groups means in academic achievement and studyskills. The statistical results indicated the effectiveness of a remedial counselling program in study skillson enhancing the academic achievement and study skills for the experimental group.